Pengaruh Sistem Penanaman Dan Pendangiran Terhadap Hasil Padi Pada Periode Transisi Organik - Noldin M. Abolla (Politeknik Pertanian Negeri Kupang, 2012)
Effect Of Cropping System And Rotating Hoe On Rice Yield At Organic Trancition Period. The increasing of food demand, such as rice is caused by population growth. Rice production can be increased through improvements in land cultivation and the improvement of the rotating hoe system. The aims of this research were to determine the effect of interaction between two cropping systems and rotating hoe to yield of rice. This research was conducted at Srihardono, Bantul Yogyakarta from June to October 2010. This research was aranged in Split Plot design with three blocks replications. The main plots were rotating hoe consisted of without rotating hoe and rotating hoe. The sub plots were cropping systems, which consisted of 20 cm x 20 cm (square cropping system), 25 cm x 25 cm (square cropping system), (30+10) cm x 10 cm (legowo cropping system) and (40+10) cm x 10 cm (legowo cropping system). All data were analyzed using Anova 5 %, followed by DMRT analysisÂ 5% when there was any difference among treatments. The result showed that the effect of the interaction between cropping system and rotating hoe was significantly different on plant growth, but it was not significantly different on the yield crop. The interaction between cropping system and rotating hoe significantly influenced differently on plant growth rate, plant-dried weight and age of flowering, but was not significantly different on panicle length, panicle number, grain number/panicle, per cent of grain content, weight of 1000 grain and actual yield. Square cropping system 25 cm x 25 cm without rotating hoe wasÂ more efficientÂ with actual yield i.e. 7.03 tones/ha compared to the legowo cropping system with rotating hoe. Key words: rice, rotating hoe, cropping system, square, legowo, growth, rice yield. Rachat de véhicule sans contrôle technique https://rachatvotrevoiture.com/rachat-de-vehicule-sans-controle-technique/